Identification and Verification of m7G Modification Patterns and Characterization of Tumor Microenvironment Infiltration via Multi-Omics Analysis in Clear Cell Renal Cell Carcinoma - Dong, Kai; Gu, Di; Shi, Jiazi; Bao, Yewei; Fu, Zhibin; Fang, Yu; Qu, Le; Zhu, Wentong; Jiang, Aimin; Wang, Linhui (Frontiers in Immunology, 2022)
The epigenetic modification of tumorigenesis and progression in neoplasm has been demonstrated in recent studies. Nevertheless, the underlying association of N7-methylguanosine (m7G) regulation with molecular heterogeneity and tumor microenvironment (TME) in clear cell renal cell carcinoma (ccRCC) remains unknown. We explored the expression profiles and genetic variation features of m7G regulators and identified their correlations with patient outcomes in pan-cancer. Three distinct m7G modification patterns, including MGCS1, MGCS2, and MGCS3, were further determined and systematically characterized via multi-omics data in ccRCC. Compared with the other two subtypes, patients in MGCS3 exhibited a higher clinical stage/grade and poorer prognosis. MGCS1 showed the lowest enrichment of metabolic activities. MGCS2 was characterized by the suppression of immunity. We then established and validated a scoring tool named m7Sig, which could predict the prognosis of ccRCC patients. This study revealed that m7G modification played a vital role in the formation of the tumor microenvironment in ccRCC. Evaluating the m7G modification landscape helps us to raise awareness and strengthen the understanding of ccRCC’s characterization and furthermore, to guide future clinical decision making.